Targeting bean research in the face of drought and climate change - Katungi, Enid M.; Farrow, Andrew (International Center for Tropical Agriculture, 2009)
Climate change will cause shifts in the areas suitable for cultivation of a wide range of crops including beans (Jarvis and Lane, 2007). Sub-Saharan Africa will be the region most affected. While annual rainfall is likely to increase in East Africa due to climate change there is less consensus on variability of rainfall between and within seasons (van de Steeg et al, 2008). Nevertheless climate change is predicted to have serious adverse effects on the agriculture of Kenya (Kabubo-Mariara and Karanja, 2006). Drought and floods will increase, particularly in arid and semi-arid areas.